Prolonged survival in stage III melanoma with ipilimumab adjuvant therapy - Eggermont, Alexander; Chiarion-Sileni, Vanna; Grob, Jean-Jacques; Dummer, Reinhard; Wolchok, Jedd D.; Schmidt, Henrik; Hamid, Omid; Robert, Caroline; Ascierto, Paolo A.; Richards, Jon M.; Lebbé, Céleste; Ferraresi, Virginia; et al. (The New England journal of medicine, 2016)
Ipilimumab, a fully human monoclonal antibody that blocks cytotoxic T-lymphocyte antigen 4 (CTLA-4) to augment antitumor immune responses, was approved by the Food and Drug Administration (FDA) and the European Medicines Agency in 2011 at a dose of 3 mg per kilogram of body weight for the treatment of advanced melanoma.1,2 On the basis of data from a phase 2 trial that indicated the potential for a dose of 10 mg per kilogram to have higher efficacy than the dose of 0.3 mg or 3 mg per kilogram in patients with advanced melanoma, although at a cost of more . . .